Contesting Double Genealogy: Representing Rebellion Ambiguity in Babad Tanah Jawi - Fawaid, Achmad (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2015)
Since firstly written in 1612 until the “final version” in 1836, Babad Tanah Jawi had a special place among intellectual debates, partly, in regard with its “functions” as mythical genre, ancient prophecy, historical narrative of Java, genealogical  prototype,  and  typical  structure  with  previous  texts.  However, little attention was given to the fact that Mataram, largely depicted in Babad Tanah Jawi, is considered as having ‘problematic’ double genealogy, which partly resulted from a double familial lineage of Batara Guru and the Prophet Adam, and the synthetic power of Demak and Majapahit. This study attempts to depict a scholarly contestation of the double genealogy of Mataram and its implication on ambivalent narratives of rebellion in the text.  Constructed as ex post  facto  in  the  universum  of  historical  references,  Babad  Tanah  Jawi seemingly  takes  its  dual  position  in  providing  a  subjectively  constructed cosmology of Javanese characters and in attempting to objectively illustrate historical  events.  In  some  ways,  it  impacts  on  the  way  the  text  justified Javanese  rulers  by  providing  supernatural  genesis  of  ancestors,  and‘purifying’ genealogical defects. The result is a distorted story of those who failed and succeeded to take over the Javanese kingdoms. The ambiguity lies on the way it has to maintain mythological genealogy of rebelling descendants and to perceive such rebellion as subversive.